(untitled) (Huellas, 2019)
The contribution of historical hydrogeomorphology in areas lacking hydrographic information or reliable geomorphological studies represents an interesting complementary tool to delimit potentially floodable spaces. This work aims at determining floodable areas through the historical hydrogeomorphological approach. The unit of analysis taken is the San Bernardo stream basin which is located in the mountain range system of Ventania, Buenos Aires (Argentina). The methodology used is based on different methods and techniques (hydrographic, geomorphologic, biogeographic) which, by complementing one another, allow for the zoning of the flood plain. The flooding events occurring in this area are linked to torrential rainfall events. The consequences range from material damage, to loss of infrastructure and even fatalities, in some cases.